A lightweight middleware for an e-health WSN based system using Android technology - Mohammed, Boulmalf; Ahmed, Belgana; Tayeb, Sadiki; Sara, Hussein; Tarik, Aouam; Hamid, Harroud (2012 International Conference on Multimedia Computing and Systems, 2012)
With the rapid development of Wireless Sensors Network (WSN) technology, together with its growing market due to the variety of applications in which this technology can be used, sensors are now available at very cheap prices, and relatively high quality. The medical field among other fields is one of the most promising fields in which sensors technology is undergoing great improvements. With the constant and continuing advances on the wireless sensor networks and applications, lots of medical applications that use sensors are emerging. Varying from pre-hospital, in-hospital applications to post-hospital and rehabilitation applications, sensors are used in a wide range of applications such as patient's drug administration to elderly remote supervision. With the lake of standardization, a framework that would govern the interaction between the applications and the network is a must to be capable of sensing, processing, and communicating vital health signs. In this research we proposed layered approach architecture for a lightweight portable middleware with the Android technology. Our system takes into consideration the design principles and issues related to medical applications. A prototype of the lightweight middleware for an e-Health WSN based System was designed and tested and we showed that the results are very promising
Keywords: WSNs; body area networks; health monitoring; Zigbee; Android; Midlleware